Airborne Spread of Methicillin Resistant Staphylococcus aureus From a Swine Farm - Angen, Øystein; Nielsen, Martin Weiss; Løfstrøm, Per; Larsen, Anders Rhod; Hendriksen, Niels Bohse (Frontiers in Veterinary Science, 2021)
Spread of livestock-associated methicillin resistant Staphylococcus aureus (LA-MRSA) to farmworkers has been recognized as a risk when working in LA-MRSA positive stables, due to LA- MRSA being present on airborne dust particles. Based on this, airborne spread of LA-MRSA through stable vents is a concern that is addressed in this study. The aim of the investigation was to quantify the airborne spread of LA-MRSA from a MRSA positive swine farm. In order to achieve this, a method for sampling large volumes of air was applied. The results were compared to meteorological data and bacteriological investigation of samples from the air inside the swine barn, soil outside the farm, and nasal samples from the individuals participating in the sampling process. MRSA was detected up to 300 m (the maximal measuring distance) from the swine farm in the air but only at low levels at distances above 50 meters (0.085 CFU/m3 at a distance of 50 m in the wind plume). MRSA was detected in sock samples obtained at the soil surfaces up to 400 m (the maximal measuring distance) from the farm building. The proportion of MRSA positive soil samples decreased from approximately 80% to 30% with increasing distance from the farm. A total of 25 human nasal samples were sampled after the farm visits after the participants had stayed in the surroundings of the farm for an average of 10.5 hours. When leaving the farm, only two of the samples (8%) were LA-MRSA-positive both obtained from one individual who was the one who had sampled the ventilation shafts. In conclusion, airborne spread of MRSA from swine farms does not seem to be an important route for human contamination for individuals staying a whole working day outside a swine farm.